PENGELOLAAN SARANA DAN PRASARANA GUNA MENUNJANG SEKOLAH YANG BERKUALITAS DI TAMAN KANAK-KANAK - Cantik Ajeng Srirahyu; Cucu Atikah; Fadlullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of facilities and infrastructure is an important aspect of early childhood education, as it helps create a safe and comfortable learning environment that supports children's development. This study aims to describe the management of facilities and infrastructure and identify its supporting and inhibiting factors at KB-TK Labschool Jakarta Timur. The study is based on the theory of educational facilities and infrastructure management, which includes planning, procurement, inventory, utilization, maintenance, supervision, and evaluation. A qualitative descriptive approach was employed, involving the principal, vice principal, teachers, administrative staff, and parents as research subjects. Data were collected through observation, interviews, documentation, and field notes, and analyzed using the Miles and Huberman model. The findings show that facilities and infrastructure management at KB-TK Labschool Jakarta Timur has been implemented systematically and contributes to the quality of learning. However, challenges remain in classroom and storage arrangement, as well as inventory management. Supporting factors include budget availability, flexible procurement policies, and cooperation among school stakeholders, while inhibiting factors relate to funding, procurement, inventory management, and maintenance. Effective management of facilities and infrastructure is therefore essential for improving the quality of early childhood education services. Keywords: facilities and infrastructure management; early childhood education; kindergarten; educational quality; educational management